THE RIGHT OF CITIZENS TO KEEP AND BEAR GUNS: A VIOLATION OF THE ARTICLE 3 AND 25 OF THE UNIVERSAL DECLARATION OF HUMAN RIGHTSSTUDY CASE OF USA, SOUTH AFRICA, FRANCE AND INDIARECOMMENDATIONS TO UNITED NATIONS BASED ON CHINA'S EXPERIENCE. Issue 3 (2020) - Mapa, Jonathan Gell; Hemed, Ali Massoud; Santos, Carlos Alves Dos; Khaskheli, Mohamed Bilawal; Saleem, Hafiz Abdul Rehman; Ying, Bi
No abstract available